Screening and Identification of the Host Proteins Interacting with Toxoplasma gondii Rhoptry Protein ROP16 - Pan, Ming; Zhou, Yanqin; Wang, Yifan; Li, Longjiao; Song, Yongle; Hou, Lun; Zhao, Junlong (Frontiers in Microbiology, 2017)
Toxoplasma gondii, as a zoonotic protozoan parasite, develops sophisticated strategies to manipulate hosts for efficient intracellular survival. After successful invasion, T. gondii injects many effector proteins into host cells for various purposes. TgROP16, which is secreted from rhoptries into host cells, can activate the host STAT signaling pathway through phosphorylation of STAT3 and STAT6. However, whether there are other host proteins modulated by TgROP16 is currently unknown. In this study, yeast two-hybrid screen was used to look for additional host proteins interacting with TgROP16. Yeast cells expressing a mouse cDNA library cloned into the prey vector were used to mate with yeasts expressing ROP16 without signal peptide. Two mouse proteins, Dnaja1 and Gabra4 were identified to interact with ROP16 from this screen. Further analysis suggested that the Predomain of ROP16 played key roles in mediating interactions with these host proteins, whereas the contribution from the Kinase domain was minor. The interactions between Dnaja1 and different parts of ROP16 were also estimated in vivo by co-immunoprecipitation. The results showed that the Predomain of ROP16 was the major region to interact with Dnaja1, which is consistent with the yeast two-hybrid results. Based on the gene ontology analysis, Dnaja1 is predicted to participate in stress response while Gabra4 is involved in the system development process. The discovery of new host proteins that interact with ROP16 of Toxoplasma gondii will help us to further investigate the functions of this effector proteins during T. gondii infection.